2012
DOI: 10.1002/nur.21512
|View full text |Cite
|
Sign up to set email alerts
|

Predictive abilities of the STOP‐Bang and Epworth Sleepiness Scale in identifying sleep clinic patients at high risk for obstructive sleep apnea

Abstract: This study compared the predictive abilities of the STOP-Bang and Epworth Sleepiness Scale (ESS) for screening sleep clinic patients for obstructive sleep apnea (OSA) and sleep-disordered breathing (SDB). Forty-seven new adult patients without previous diagnoses of OSA or SDB were administered the STOP-Bang and ESS and were assigned to OSA or SDB risk groups based on their scores. STOP-Bang responses were scored with two Body Mass Index cut points of 35 and 30 kg/m(2) (SB35 and SB30). The tools' predictive abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 37 publications
4
33
0
5
Order By: Relevance
“…An evaluation of the Croatian version of STOP questionnaire using a cutoff value of 2 in the screening tool showed sensitivity of 96 %, specificity of 83 %, PPV of 61 %, and NPV of 95 % against AHI>5 [15]. Another study involving high-risk patients found a sensitivity of 93.8 %, specificity of 33.3 %, PPV of 75 %, and NPV of 71.4 % against AHI>5 [14]. These differences in predictive parameters may be due to differences in study population characteristics, morbidities, and differences in methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation of the Croatian version of STOP questionnaire using a cutoff value of 2 in the screening tool showed sensitivity of 96 %, specificity of 83 %, PPV of 61 %, and NPV of 95 % against AHI>5 [15]. Another study involving high-risk patients found a sensitivity of 93.8 %, specificity of 33.3 %, PPV of 75 %, and NPV of 71.4 % against AHI>5 [14]. These differences in predictive parameters may be due to differences in study population characteristics, morbidities, and differences in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of eight independent questions with a score of 3 or more indicating high-risk patients for OSA. Vana and colleagues [14] concluded in their study that STOP-Bang could identify more patients with OSA than ESS in a sleep clinic setting with a sensitivity of 94.7 % compared to a sensitivity of 26.3 % in ESS. Another study by Pecotic and others showed that STOP-Bang had better probability to correctly predict high-risk patients for OSA compared to ESS [15].…”
mentioning
confidence: 99%
“…Even screening tools that work well in subjects without HF such as the Epworth Sleepiness Scale have not proven reliable in patients with HF 38. Other screening questionnaires are the Berlin Questionnaire39, 40 and the STOP‐Bang Sleep Apnea Questionnaire,41, 42, 43, 44 but both have not been validated in patients with HF. The severity of the disease can be screened for using two indices: The Apnoe–Hypopnoe Index (AHI) and Oxygen Desaturation Index (ODI).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Patients with poor functional capacity (<4 METS) or have at least intermediate clinical predictors for a cardiac event (mild angina pectoris, prior myocardial infarction, compensated or prior CHF, diabetes mellitus, and renal insuffi ciency) are often evaluated with an echocardiogram or dobutamine stress echocardiogram as indicated as well as consideration for the use of perioperative beta blockade. Patients with a BMI > 50 or an Epworth sleepiness scale > 10 are routinely referred for polysomnography and consultation with sleep medicine to evaluate need for a continuous positive airway pressure (CPAP) device [ 41 ]. The number of nutritional sessions (range 3-6 months) is typically designated by different insurance carriers.…”
Section: Cleveland Clinic Protocolmentioning
confidence: 99%